2013
DOI: 10.1007/s10059-013-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stress Responsive Rice ASR1 and ASR3 Exhibit Different Tissue-Dependent Sugar and Hormone-Sensitivities

Abstract: The expression of the six rice ASR genes is differentially regulated in a tissue-dependent manner according to environmental conditions and reproductive stages. OsASR1 and OsASR3 are the most abundant and are found in most tissues; they are enriched in the leaves and roots, respectively. Coexpression analysis of OsASR1 and OsASR3 and a comparison of the cis-acting elements upstream of OsASR1 and OsASR3 suggested that their expression is regulated in common by abiotic stresses but differently regulated by hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 93 publications
1
44
0
Order By: Relevance
“…The characteristics of the cis-acting elements present in the regulatory regions of OsAsr1 and OsAsr3 suggest that stress, sugar and hormones are the key regulators of the expression of these rice paralogs. 18 In the same line, P erez-D ıaz et al 46 found that OsAsr1, OsAsr2 and OsAsr3 regulatory regions have a motif of sugar repression, whereas all rice ASR paralogs (Asr1 to Asr6) have an element of sugar induction and gibberellin repression in their regulatory regions. These data suggest that other paralogs of ASR1 could be involved in sugar-hormone crosstalk as well.…”
Section: Asr1 Is Involved In Sugarhormone Crosstalk and In Sugar Signmentioning
confidence: 98%
See 2 more Smart Citations
“…The characteristics of the cis-acting elements present in the regulatory regions of OsAsr1 and OsAsr3 suggest that stress, sugar and hormones are the key regulators of the expression of these rice paralogs. 18 In the same line, P erez-D ıaz et al 46 found that OsAsr1, OsAsr2 and OsAsr3 regulatory regions have a motif of sugar repression, whereas all rice ASR paralogs (Asr1 to Asr6) have an element of sugar induction and gibberellin repression in their regulatory regions. These data suggest that other paralogs of ASR1 could be involved in sugar-hormone crosstalk as well.…”
Section: Asr1 Is Involved In Sugarhormone Crosstalk and In Sugar Signmentioning
confidence: 98%
“…Among others, this increase occurs in tobacco and tomato by osmotic and drought stress; 4,16,[20][21][22] in rice by drought, saline and osmotic stress; 10,23,24,25 and in plantain and banana by osmotic and biotic stress. 11,26,27 Only a few physiological studies with transgenic tomato, 28 tobacco, 22 maize, 29 and rice 18 plants have proved the involvement of ASR1 in stress tolerance.…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
See 1 more Smart Citation
“…Several orthologous and paralogous ASR genes have been found to be transcriptionally regulated by ABA and sugar signaling (Amitai-Zeigersona et al 1995;Çakir et al 2003;Kalifa et al 2004;Liu et al 2010;Chen et al 2011;Henry et al 2011;Virlouvet et al 2011;Joo et al 2013). Additionally, overexpression of some ASR genes resulted in reduced sensitivity to ABA and changed transcription levels of ABA/ stress-responsive genes (Yang et al 2005;Shkolnik and BarZvi 2008).…”
Section: Introductionmentioning
confidence: 93%
“…The plasmids were introduced into Agrobacterium tumefaciens LBA4404 through triparental mating, and embryogenic calli from mature rice seeds were transformed. The callus induction, co-cultivation with A. tumefaciens and selection of transformed calli were performed (Joo et al 2013).…”
Section: Plasmid Construction and Transformation Of Ricementioning
confidence: 99%